If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -7) + -1(6 + -1x) = 4 + -1(x + -5) Reorder the terms: 2(-7 + 3x) + -1(6 + -1x) = 4 + -1(x + -5) (-7 * 2 + 3x * 2) + -1(6 + -1x) = 4 + -1(x + -5) (-14 + 6x) + -1(6 + -1x) = 4 + -1(x + -5) -14 + 6x + (6 * -1 + -1x * -1) = 4 + -1(x + -5) -14 + 6x + (-6 + 1x) = 4 + -1(x + -5) Reorder the terms: -14 + -6 + 6x + 1x = 4 + -1(x + -5) Combine like terms: -14 + -6 = -20 -20 + 6x + 1x = 4 + -1(x + -5) Combine like terms: 6x + 1x = 7x -20 + 7x = 4 + -1(x + -5) Reorder the terms: -20 + 7x = 4 + -1(-5 + x) -20 + 7x = 4 + (-5 * -1 + x * -1) -20 + 7x = 4 + (5 + -1x) Combine like terms: 4 + 5 = 9 -20 + 7x = 9 + -1x Solving -20 + 7x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -20 + 7x + x = 9 + -1x + x Combine like terms: 7x + x = 8x -20 + 8x = 9 + -1x + x Combine like terms: -1x + x = 0 -20 + 8x = 9 + 0 -20 + 8x = 9 Add '20' to each side of the equation. -20 + 20 + 8x = 9 + 20 Combine like terms: -20 + 20 = 0 0 + 8x = 9 + 20 8x = 9 + 20 Combine like terms: 9 + 20 = 29 8x = 29 Divide each side by '8'. x = 3.625 Simplifying x = 3.625
| 25(2x-1)=6(x+3)+3x | | v=4/3Π×9^ | | Z/1.6=1.1 | | 4x^3+2x^2+0.25x=0.173 | | x^2-y^2=201 | | 2=(x-1.97)/1.97 | | 2x-1/x^2=0 | | ln(4x^2)+ln(8)=5 | | 4/3•3.14•8 | | 8+7=12x-3-8x+1 | | 3x/7=10-x/2 | | y+7x=32 | | x^(3/4)=4 | | 2b+3(3b+19)=25 | | 2y-3x=-48 | | 3x+2y=-48 | | (4C-1)(5C+3)=0 | | xNy=2xy^2 | | 11x(751+209)= | | -2+5x=3x | | (-3b-1/4)-8 | | 8-2(7x-4)=6x-4 | | y=e^4lnx | | 204-(577-512)= | | 207-(577-512)= | | x^2+6x-36=-3 | | .33(9-6x)=x | | tan(x)=3.7 | | 12t^2-24t=0 | | 18*(480+859)= | | 7/x=3/4 | | X^2-12x-21=10 |